Resistensi Nelayan dalam Pembangunan PLTU Cilacap Desa Menganti Kecamatan Kesugihan Kabupaten Cilacap - Elsa Fitrianita; Nurdien Harry Kistanto; Af'idatul Lathifah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
This research was conducted to find out and describe the resistance of Menganti Kisik fihermen in the construction of the PLTU Cilacap in Menganti Village, Kesugihan District, Cilacap Regency, analyzing the sources and forms that caused the resistance of Menganti fihermen to the construction of the PLTU Cilacap  and how the strategies to survive and efforts to resolve the conflict. The research method used is the ethnographic method. This research was conducted in March to May in the coastal area of Menganti Village, Menganti Kisik. The data collection techniques are carried out by means of observation, ethnographic interviews, and documentation. The data analysis techniques were carried out in an ethnographic manner with qualitative descriptions. The results of the study showed that the resistance of the Menganti Kisik fishermen occurred due to the perceived loss in the social, economic and physical sectors due to the construction of the PLTU Cilacap. Fishermen choose the hidden transcript resistance and collective resistance. The fishermen do the resistance is because of  the imbalance of the work space sector and damage to the coastal and marine areas which cause coastal abrasion in Menganti Village. The kind of resistance are include the differences in perceptions between fishermen in responding to the construction of the PLTU Cilacap, compensation polemics, and expressions of resistance. The strategy of surviving fishermen in the midst of losses due to the construction of the PLTU Cilacap is to establish a social organization KUPM Menganti Kisik which is used as a medium of collective resistance.